Nilai Pendidikan Al-Ijaz fī Jawāmi' al-Kalim: Efisiensi Bahasa Hadis Nabi dalam Pembentukan Akhlak - Muh. Mukhlis Rahman; Haniah (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2026)
The prophetic linguistic phenomenon of al-ijaz fī jawāmiʿ al-kalim, the concise yet profoundly meaningful expressions of the Prophet Muhammad saw. The study emerges from the gap in existing literature, where discussions on jawāmiʿ al-kalim often focus narrowly on linguistic aesthetics rather than its integrative moral and educational dimensions. This research synthesizes classical and contemporary perspectives to reveal how brevity in prophetic discourse functions as a transformative medium for ethical, spiritual, and social development. Methodologically, this study employs a systematic literature review by analyzing primary hadith sources, classical balāghah texts, and modern scholarly interpretations, followed by thematic coding and conceptual synthesis. The findings indicate that jawāmiʿ al-kalim encapsulates intertwined moral values, ethical responsibility, self-discipline, spiritual consciousness, and interpersonal harmony conveyed through rhetorical devices such as ijaz al-qaṣr and ijaz al-ḥadhf. These linguistic strategies enable the timeless transmission of moral principles in minimal words. The research concludes that the Prophet’s rhetorical style represents a moral pedagogy rooted in eloquence, simplicity, and universality. Theoretically, it bridges linguistic analysis and moral education, offering a model for ethical communication and character formation relevant to contemporary contexts. This study strengthens the conceptual foundation of Islamic moral linguistics and its educational applications.